Response of tomato fruit to consecutive impact loading - Ghaffari-Setoubadi, Hossein; Ghassemzadeh, Hamid-Reza; Mohammadi-Ghermezgoli, Khosro; Rafat, Seyed Abbas; Halimi-Milani, Omid (Journal of Aridland Agriculture, 2024)
Tomato fruits receive successive impacts during harvest and postharvest operations. This paper is a study of the response of tomato fruit to mono and multiple dynamic loadings and the ability to withstand consecutive impacts, which play the most critical role in downgrading and postharvest loss of fresh tomato fruits and designing harvest, and postharvest handling and processing equipment. The fruits were subjected to consecutive impacts by an instrumented pendulum one to three times successive impacts at the same location with the three different impact energy levels: 125, 250, and 500 mJ to establish a comprehensive model and refining by adding various groups of contributing factors to understand better and find out which parameters are more likely to cause and contribute in tomato mechanical damage. Twenty sub-models were evaluated using AIC and R2 values. The parameters of the preferred logistic model consist of response variables (peak contact force, contact time, and Elast), loading conditions (one, two, and three-times impact at the same location), and fruit quality parameter (total soluble solids). Also, another model was suggested for rapid assessment of bruise development.